2007
DOI: 10.1097/jom.0b013e318156eca3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Lipids and Liver Enzymes Related to a Serum Biomarker of Exposure (ammonium perfluorooctanoate or APFO) as Part of a General Health Survey in a Cohort of Occupationally Exposed Workers

Abstract: Our findings indicate a modest positive association of PFOA on some lipid parameters and a need for follow-up studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 35 publications
4
134
1
Order By: Relevance
“…However, those data are not always consistent. One cross-sectional study carried out among occupational population with a much higher exposure level observed a modest but statistically significant, positive relationship between serum PFOA and TC, LDLC, for each increase in 1 ng/mL in serum PFOA, TC and LDLC increases by 0.10 Â 10 À 3 and 0.07 Â 10 À 3 mmol/L, respectively (Sakr et al, 2007a). In a longitudinal study, Sakr et al (2007b) found serum PFOA was positively associated with TC, with an increase of 0.03 Â 10 À 3 mmol/L of cholesterol for each 1 ng/mL increase in PFOA.…”
Section: Discussionmentioning
confidence: 99%
“…However, those data are not always consistent. One cross-sectional study carried out among occupational population with a much higher exposure level observed a modest but statistically significant, positive relationship between serum PFOA and TC, LDLC, for each increase in 1 ng/mL in serum PFOA, TC and LDLC increases by 0.10 Â 10 À 3 and 0.07 Â 10 À 3 mmol/L, respectively (Sakr et al, 2007a). In a longitudinal study, Sakr et al (2007b) found serum PFOA was positively associated with TC, with an increase of 0.03 Â 10 À 3 mmol/L of cholesterol for each 1 ng/mL increase in PFOA.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer mortality [11] Liver tumors, pancreatic acinar cell tumors, Leydig cell tumors [79] Hepatotoxicities Slight increases in total cholesterol, lowdensity lipoprotein, very low-density lipoprotein, gamma glutamyl aminotransferase, and aspartate aminotransferase [77] Hepatomegaly accompanied by mitochondrial proliferation, no peroxisome proliferation [85] Peroxisome proliferation, increased hepatocyte hypertrophy, increased labeling index [83] Developmental toxicities…”
Section: Pfoa Carcinogenicitymentioning
confidence: 99%
“…An association between perfluorooctane sulphonate ⁄ perfluorooctanoic acid (PFOA) levels and serum cholesterol was found in a large US cross-sectional study [60]. In a crosssectional study of 1025 workers with potential exposure to PFOA, the circulating levels of this compound were related to LDL cholesterol concentration [61].…”
Section: Lipidsmentioning
confidence: 99%